Genome-Wide Comprehensive Survey of the Subtilisin-Like Proteases Gene Family Associated With Rice Caryopsis Development - Zheng, Kaifeng; Pang, Lu; Xue, Xiuhua; Gao, Ping; Zhao, Heping; Wang, Yingdian; Han, Shengcheng (Frontiers in Plant Science, 2022)
Subtilisin-like proteases (SUBs), which are extensively distributed in three life domains, affect all aspects of the plant life cycle, from embryogenesis and organogenesis to senescence. To explore the role of SUBs in rice caryopsis development, we recharacterized the OsSUB gene family in rice (Oryza sativa ssp. japonica). In addition, investigation of the SUBs was conducted across cultivated and wild rice in seven other Oryza diploid species (O. brachyantha, O. glaberrima, O. meridionalis, O. nivara, O. punctata, O. rufipogon, and O. sativa ssp. indica). Sixty-two OsSUBs were identified in the latest O. sativa ssp. japonica genome, which was higher than that observed in wild species. The SUB gene family was classified into six evolutionary branches, and SUB1 and SUB3 possessed all tandem duplication (TD) genes. All paralogous SUBs in eight Oryza plants underwent significant purifying selection. The expansion of SUBs in cultivated rice was primarily associated with the occurrence of tandem duplication events and purifying selection and may be the result of rice domestication. Combining the expression patterns of OsSUBs in different rice tissues and qRT–PCR verification, four OsSUBs were expressed in rice caryopses. Moreover, OsSUBs expressed in rice caryopses possessed an earlier origin in Oryza, and the gene cluster formed by OsSUBs together with the surrounding gene blocks may be responsible for the specific expression of OsSUBs in caryopses. All the above insights were inseparable from the continuous evolution and domestication of Oryza. Together, our findings not only contribute to the understanding of the evolution of SUBs in cultivated and wild rice but also lay the molecular foundation of caryopsis development and engineering improvement of crop yield.